The Role of Value Stream in Measuring Environmental Costs and Reducing Costs - Shaker Dhari, Saba; Ahmed Nouri, Muqdad (Journal of Economics and Administrative Sciences, 2024)
Most economic units suffer from high rates of environmental pollution and a shortage of available resources and energy. This iead to a significant increase in production costs. In addition the economic units  lack of using modern cost methods through which environmental costs and production costs are identified, allocated and measured. One of these methods is the value flow method . which works to track production processes, analyze inputs and outputs, and classify them into sound products and unhealthy products (waste).This in turn  enables management to identify value-added activities and non-value-added activities, and works to reduce environmental impacts, the amount of waste, and reduce losses that occur during production, Therfure the production process and optimal exploitation of resources, reduce  product costs and producing environmentally friendly products, and this leads to improving environmental performance in Iraqi economic units. The research aims to restructure the economic unit, which is managed through its departments and manage it according to the value flow method and to calculate environmental costs. For the purpose of achieving the objectives of this study and testing the hypotheses, the General Company for Heavy Engineering Equipment waschosen.The sample is one of the companies of the Ministry of Oil . relying on the financial and non-financial data that it included. Reports and records for the year 2021-2022.as well as field consultation and deliberation of questions with engineers, specialists and workers to benefit from their accumulated experience.The collected data are  anaiysed  according to value flow cost accounting in order to improve the production process, and in order to reduce environmental impacts, the amount of waste and emissions, and optimal exploitation of resources and energy. The most important conclusions reached by the researcher were the ability of the value flow to calculate the environmental costs of each flow within the economic unit, as well as providing more accurate and objective data and information for making decisions and measuring the performance of the economic unit to contribute to monitoring environmental activities and the possibility of reducing the costs of those activities.